2019
DOI: 10.1097/sle.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy Versus Open Incarcerated Inguinal Hernia Repair in Octogenarians: Single-Center Experience With World Review

Abstract: Objectives: The clinical study is aiming to discuss the therapeutic benefit of laparoscopic hernia (LH) repair with comparing conventional open hernia (OH) repair in incarcerated hernia in octogenarians. Materials and Methods: The clinical data of 29 octogenarian incarcerated hernia patients who underwent hernia repair from November 2013 to March 2017 were retrospectively analyzed. The variables analyzed include baseline, operation characteristics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…It also allows the inspection of female reproductive organs, such as ovaries, fallopian tubes, and uterus. 28 , 35 In our material, we observed the complete androgen insensitivity syndrome (CAIS), 36 where male gonads moved to inguinal canals on both sides in phenotypically 4-year-old girl. 21 , 23 In laparoscopy, it is possible to observe the disorders in the bowel movement, determine the presence of the Meckel’s diverticulum (a similar case was discussed by Quail et al) 37 and to assess the position of the appendix.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It also allows the inspection of female reproductive organs, such as ovaries, fallopian tubes, and uterus. 28 , 35 In our material, we observed the complete androgen insensitivity syndrome (CAIS), 36 where male gonads moved to inguinal canals on both sides in phenotypically 4-year-old girl. 21 , 23 In laparoscopy, it is possible to observe the disorders in the bowel movement, determine the presence of the Meckel’s diverticulum (a similar case was discussed by Quail et al) 37 and to assess the position of the appendix.…”
Section: Discussionmentioning
confidence: 72%
“…Payiziwula et al reported in early postoperative time a sliding hernia not recognized during laparoscopic inguinal hernia repair (bladder herniating into the right inguinal region, consistent with an extraperitoneal invisible, undetectable hernia). 35 …”
Section: Discussionmentioning
confidence: 99%
“…Following this screen, a total of five articles have been selected for inclusion in the final systematic review. [16][17][18][19][20] This process is illustrated in the PRISMA Flowchart as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Reporting of follow-up period varied across studies. Two studies did not report the follow-up period, 16,17 one study reported a 2.3 year median follow-up, 19 one study reported a mean follow-up period of 24 (laparoscopic group) to 25 (open group) months 20 while one study reported 96% of patients completing a 60-month follow-up period. 18…”
Section: Descriptive Characteristics Of the Included Articlesmentioning
confidence: 99%
“…However, incarcerated hernia contents may return to the abdominal cavity owing to anesthetics and muscle relaxants, leading to potential necrotic contents that may lead to intestinal perforation, abdominal infection, or fatal sepsis. The introduction of laparoscopic techniques has greatly sharpened the surgical paradigm and is more prevalent in hernia surgery, with plausible clinical outcomes [9] . Using a laparoscope can facilitate the direct assessment of an incarcerated bowel, and the viability of the bowel can be evaluated [10] .…”
Section: Discussionmentioning
confidence: 99%